Contesting Global Civil Society’s Legitimacy Claims: Evaluating International Non-Governmental Organizations (INGOs)’ Representation of and Accountability to Beneficiaries - Tamzil, Cazadira Fediva (Global: Jurnal Politik Internasional, 2016)
The global civil society is often regarded as a progressive moral force that provides advocacy and protection of marginalized groups in the global political arena. Nevertheless, departing from the belief that civil society has great power and influence over global dynamics, it sees that the legitimacy claims they articulate and articulated by academics are essential to be evaluated, especially with regard to their representation and accountability groups and individual beneficiaries. This paper concludes that the claims of legitimacy of civil society are less justifiable, both normatively and empirically. From the normative point of view, claims for civil society representation are problematic because they are often less ethical and thus have a counterproductive effect on the benefit of beneficiaries. In addition, they are more accountable to donors and the sustainability of related institutions than the interests of beneficiaries. From the empirical point of view, the legitimacy of civil society is also questionable because it is now emerging discourses from their own beneficiaries who oppose the actions of representatives and the lack of accountability demonstrated by International Non-Governmental Organizations over Beneficiaries. This paper concludes with a recommendation to the International NGOs to put the Beneficiaries' interests as top priority and stop projecting beneficiaries as passive, mute, and without political agency.